Contribution of limestone to the hydration of calcium sulfoaluminate cement. (September 2015) - Martin, Lukas H.J.; Winnefeld, Frank; Müller, Christian J.; Lothenbach, Barbara
Abstract: Calcium sulfoaluminate (CSA) cements can be blended with mineral additions such as limestone for properties and cost optimization. This study investigates the contribution of limestone to the hydration of a commercial CSA clinker regarding the hydration kinetics, hydrate assemblage and compressive strength. Nine formulations were defined at M -values of 0, 1.1 and 2.1 ( M  = molar ratio of anhydrite to ye'elimite) without and with medium and high limestone contents. Calorimetric results indicate that limestone accelerates the hydration reaction especially at M  = 1.1, probably due to the filler effect. The phase assemblages were calculated by thermodynamic modeling using Gibbs Energy Minimization Software (GEMS). With increasing limestone content the formation of ettringite and calcium monocarboaluminate is predicted at the expense of calcium monosulfoaluminate. With increasing M -value more ettringite is predicted at the expense of the monocarbonate and less calcite takes part in the hydration reactions. The modeled results compare well with the experimental data after 90 d of hydration, except that calcium hemicarboaluminate was found instead of monocarbonate, which is assumed to be due to kinetics considerations. The lowest compressive strength occurs in ternary formulations, whereas in the absence of calcium sulfate, strength is significantly higher. The results presented here indicate that in CSA cements, limestone accelerates early hydration kinetics, takes part in the hydration reactions at M  < 2, and has a positive effect on strength development in systems without anhydrite.